Midesophageal Metastatic Disease After Treatment of Gastroesophageal Junction Adenocarcinoma. Issue 10 (6th October 2022) - Brotherton, Tim; Burton, Sam; Knoche, Eric; Presti, Michael
ABSTRACT: Esophageal cancer carries a significant risk of morbidity and mortality because of its poor prognosis. Adenocarcinoma is the most common type of esophageal cancer in the United States. Local metastasis within the esophagus is extremely rare and likely because of the complex esophageal lymphatic system. Our patient is a 74-year-old man with adenocarcinoma of the gastroesophageal junction treated with chemotherapy and radiation who was subsequently found to have local metastasis to the proximal esophagus.